The role of globalization in modulating the effect of environmental degradation on inclusive human development - Simplice Asongu; Nicholas M. Odhiambo (African Governance and Development Institute (AGDI), 2020)
This study assesses how globalisation modulates the effect of environmental degradation on inclusive human development in 44 countries in Sub-Saharan Africa (SSA), using data for the period 2000 to 2012. The empirical results are based on the Generalized Method of Moments (GMM). The following main findings are established. First, a trade openness (imports + exports) threshold of between 80-120% of GDP is the maximum level required for trade openness to effectively modulate CO2 emissions (metric tonnes per capita) and induce a positive effect on inclusive human development. Second, a minimum threshold required for trade openness to modulate CO2 intensity (kg per kg of oil-equivalent energy use) and induce a positive effect on inclusive human development is 200% of GDP. Third, there is a net positive effect on inclusive human development from the relevance of trade openness in modulating the effect of CO2 emissions per capita on inclusive human development and a negative net effect on inclusive human development from the importance of trade openness in moderating the effect of CO2 intensity on inclusive human development.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; Economic development; Africa